Avaliação da fosforilação da AKT e do conteúdo da proteína transportadora de glicose GLUT4 em tecido muscular esquelético de ratos adultos, proles de ratas com doença periodontal - Mattera, Maria Sara de Lima Coutinho [UNESP] (2015)
The fetal programming hypothesis suggests that intrauterine stimuli or aggression can induce metabolic and physiology changes in offspring, increasing the diseases risk in adulthood. Studies have demonstrated that periodontal disease (PD) and adipose tissue augmentation enhance the cytokines levels. Cytokines such as TNF-α have been associated with reduced GLUT4 expression and insulin resistance. Knowing that GLUT4 is important for glucose homeostasis, the aim of present study was to evaluate in adult rats, offspring of rats with periodontal disease: 1) birth weight and during the 75 days of age; 2) GLUT4 content and its translocation index in gastrocnemius skeletal muscle tissue (GM); 3) Akt serine phosphorylation status in MG. Female Wistar rats were distributed into a control group (CN, n = 4) and a experimental periodontal disease group (PD, n = 4), in which the disease is induced by ligation with silk thread around the 1st molar. Seven days after ligature placement, animals from both groups mated and daily vaginal smears were taken to verify the presence of sperm. Pregnant rats were kept in individual cages. The body weights of the offspring were measured once weekly from birth until 75 days of age. When male offspring of these rats completed 75 days, the experiments were performed: 1) assessment of plasma concentrations of glucose and insulin; 2) evaluation of the GLUT4 content and its translocation index in GM; 3) Akt serine phosphorylation status in GM. The results showed that maternal periodontal disease causes in their offspring low birth weight, and in adulthood: 1) no changes in glycemia; 2) increase in insulinemia; 3) insulin resistance; 4) decrease in GLUT4 content in the plasma membrane and its translocation index in GM; 5) reduction in the Akt serine phosphorylation status in GM. Therefore, we can conclude that maternal periodontal disease causes...